Parahoric restriction for GSp(4) - Rösner, Mirko (Algebras and representation theory, 2018)
Parahoric restriction is the parahoric analogue of Jacquet’s functor. The group GSp(4, F) of symplectic similitudes of genus two over a local number field F/ℚ p has five conjugacy classes of parahoric subgroups. For each we determine the parahoric restriction of the non-cuspidal irreducible smooth representations of GSp(4, F) in terms of explicit character values.
Published online: 5 July 2017
Gesehen am 20.03.2018